VERGİ HUKUKUNDA ZAMANAŞIMI KAVRAMINA YÖNELİK BİR İNCELEME - (:unkn) unknown (My University, 2014)
Zamanaşımı vergiyi doğuran olayın üzerinden kanunda belirtilen sürenin geçmesine rağmen, verginin tarh edilerek mükellefe tebliğ edilmemesi halinde söz konusudur. Ancak VUKta düzenlenen zamanaşımı ile ilgili kavramsal olarak çelişkiler bulunmaktadır. İlgili maddeler (VUK md. 113-114) zamanaşımını nitelendirme yerine sadece kapsamını belirlediğinden literatürde ifade edilen zamanaşımı kavramı, tarh tebliğ-tahakkuk-tahsil aşamalarından oluşan vergilendirme sürecini dikkate alarak; tarh zamanaşımı , tahakkuk zamanaşımı , tebliğ zamanaşımı , vergilendirme zamanaşımı ve tarh ve tebliğ zamanaşımı olarak farklı şekillerde nitelendirilmiştir. Bu çerçevede bu çalışmada öncelikli olarak zamanaşımı kavramı değerlendirilecek ve diğer kavramlar da başlıklar halinde incelenecektir.

Statute of limitation is in question, while levying the tax, not notifying the taxpayer although staturoy period has finished from the taxable event. However, relating to the statute of limitation specified in Tax Procedural Law, there are some notional contradictions. The relevant articles of Tax Procedural Law (113-114) determines only the scope of the statute of limitation rahter than qualifying it, the term statute of limitation in literature has been qulified in defferent means as limitation of tax assesment, limitation of tax accrual, limitation of notification, limitation of taxation, limitation of tax assesment and accural by considering the taxation process consists of tax assesment-tax notification-tax accrual- tax collection stages. In this context in this study, the term of statute of limitation will be examined primarily then the other terms will be discussed under the different headings.
(A REVİEW OVER THE TERM STATUTE OF LIMITATION IN TAX LAW)
Keywords: Hukuk